Short Communication: Taxonomic status of Great Argus (Argusianus argus) Sumatra and Borneo based on cytochrome B gene (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ericca C, Tjong DH, Roesma DI, Novarino W, Syafullah, Janra MN, Aandrean. 2022. Short Communication: Taxonomic status of Great Argus (Argusianus argus) Sumatra and Borneo based on cytochrome B gene. Biodiversitas 23: 4670-4676. Great Argus (Argusianus argus) belongs to the bird family Phasianidae. Currently, there are two Great Argus subspecies: A. argus argus in Sumatra and the Malay Peninsula, and A. argus grayi in Borneo. Therefore, this study aims to determine the taxonomic status of Great Argus across its distribution region. Phylogenetic relationships between two Great Argus subspecies were inferred in this study using the mitochondrial cytochrome b gene. DNA was isolated, amplified, and sequenced from the feathers of Great Argus sampled from Kinantan Wildlife and Cultural Park, Bukittinggi, West Sumatra, Indonesia. Phylogenetic relationships were analyzed with Maximum Likelihood methods. The phylogenetic trees show monophyletic relationships between Sumatran Great Argus subspecies. Analysis result shows that Bornean Great Argus has a 3.26-3.80% genetic distance from the Sumatran Great Argus based on analysis using the 789 bp of cyt b gene. Based on the result, it also refers that Bornean Great Argus and Crested Argus (Rheinardia ocellata), have a close relationship, indicated by low genetic distances (5.87-6.73%). This study suggests that Bornean Great Argus is genetically different from Sumatran Great Argus.
Keywords: cytochrome b gene; genetic distance; great argus; phylogenetic